Radical changes are needed for transformations to a good Anthropocene - McPhearson Timon; Raymond M. Christopher; Gulsrud Natalie; Albert Christian; Coles Neil; Fagerholm Nora; Nagatsu Michiru; Olafsson Stahl Anton; Soininen Niko; Vierikko Kati (Nature Publishing Group, 2022)
The scale, pace, and intensity of human activity on the planet demands radical departures from the status quo to remain within planetary boundaries and achieve sustainability. The steering arms of society including embedded financial, legal, political, and governance systems must be radically realigned and recognize the connectivity among social, ecological, and technological domains of urban systems to deliver more just, equitable, sustainable, and resilient futures. We present five key principles requiring fundamental cognitive, behavioral, and cultural shifts including rethinking growth, rethinking efficiency, rethinking the state, rethinking the commons, and rethinking justice needed together to radically transform neighborhoods, cities, and regions.